Comparative Analysis of Use and Perceived Attributes of ICTs in Public and Private Extension Systems in India - Lakher, Raksha; Rao I, Sreenivas; Meera, Shaik N. (Journal of Agricultural Extension Management, 2019)
ICT enabled extension offers new opportunities for bridging the knowledge and extension service gap in Indian agriculture. However, several critical challenges still remain. One of the most critical issues related to use of ICTs in the extension system is perceived use of ICTs within these systems. A study was conducted to know about sources of information, use of ICTs, and the perceived attributes of ICTs in private, public and other agricultural extension organizations. While planning to integrate ICTs into the extension system, it is important to consider perceived attributes of ICTs rather than the actual attributes. The results and discussions pertain to the perceived attributes of ICTs as technology per se. On the basis of these attributes, extension organizations may consider evolving ICT enabled extension strategies.